Comparative Study between Dynamic Hip Screw versus Proximal Femoral Nail Devices in the Management of Intertrochanteric Fractures - Muhammad Zeb Khan, Muhammad Rehan, Ali Salman, Malik Mohammad Yasin Awan, Ahad Kareem Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the dynamic hip screw versus proximal femoral nail devices in the management of intertrochanteric fractures Design of the Study: It was a cross-sectional survey. Place and Duration of Study: This study was carried at the Department of Orthopaedic and Spine Surgery, Sahara Medical College (Sughra Shafi Medical Complex), Narowal from April 2022 to September 2022. Patients and Methods: In this study, 70 patients of both sexes, ranging in age from 40 to 70, had intertrochanteric fracture surgery. Two treatment groups were created by randomly dividing these patients; Group-A (n=35) patients got proximal femoral nailing while Group-B (n=35) patients underwent fracture fixation with DHS. The outcome variables that were used to compare the two groups were the frequency of infection (diagnosed clinically upon appearance of any two of the following signs within 4 weeks after surgery: redness around the wound, serosangious discharge, and fever >100oF). Every participant’s signed informed permission was obtained. Results of the Study: The age of the patients ranged from 40 years to 70 years with a mean of 54.96±8.34 years. There were 28 (40%) male and 42 (60%) female patients. 46 (65.7%) patients had Type-I and 24 (34.3%) patients had Type-II fracture according to Evan’s Classification. The frequency of infection was significantly higher in the DHS group (31.4% vs. 0.0%; p=0.000) as compared to PFN group. Conclusion: In patients with intertrochanteric fractures, proximal femoral nail was found to be superior to DHS in terms of a significantly reduced risk of infection, regardless of the patient’s age or gender. This supports the preferred use of proximal femoral nail in future practise, provided the necessary hardware and surgical skills are available. Keywords: Dynamic Hip Screw, Proximal Femoral Nail, Intertrochanteric Fractures, Infection, Evan’s Classification